D-dimer trends elaborate the heterogeneity of risk in hospitalized patients with COVID-19: A multi-national case series from different waves - Ronderos Botero, Diana Maria; Omar, Alaa Mabrouk Salem; Pengo, Martino F.; Haider, Syed Waqas; Latif, Hira; Parati, Gianfranco; Pengo, Vittorio; Cañas Arboleda, Alejandra; Díaz, Melissa; Villaquirán-Torres, Claudio; Contreras, Johanna; Chilimuri, Sridhar (Frontiers in Medicine, 2023)
Introduction: Variable D-dimer trends during hospitalization reportedly result in distinct in-hospital mortality. In this multinational case series from the first and second wave, we show the universality of such D-dimer trends. Methods and results: We reviewed 405 COVID-19 patients during the first wave admitted to 3 institutions in USA, Italy, and Colombia, 111 patients admitted to the USA site during the second wave and 55 patients during the third wave. D-dimer was serially followed during hospitalization. During the first wave 66(15%) patients had a persistently low pattern, 33(8%) had early peaking, 70(16%) had mid peaking, 94(22%) had fluctuating, 30(7%) had late peaking, and 112(26%) had persistently high pattern. During the second and the third waves, similar patterns were observed. D-dimer patterns were significantly different in terms of in-hospital mortality similarly in all waves. Patterns were then classified into low-risk patterns (persistently low, and early peaking) where no deaths were observed in both waves, high risk patterns: (mid peaking and fluctuating), and malignant patterns (late peaking and persistently high). Overall, D-dimer trends were associated with an increased risk for in-hospital mortality in the first wave (Overall: HR: 1.73) and stayed the same during the second (HR: 1.67, p<0.001), and the third (HR: 4.4, p=0.001) waves. Conclusions: D-dimer behavior during COVID-19 hospitalization yielded universal categories with distinct mortality risk that persisted throughout all studied waves of infection. Monitoring D-dimer behavior may be useful in the management of these patients.